The Caravaggist and the Revival of Seventeenth Century Features in “Utrecht” Murals - Mohamed Abd El-Salam Abd El-Sadik Helal (Maǧallaẗ Al-Turāṯ wa Al-Taṣmīm, 2021)
Abstract:Michelangelo Merisi, or Caravaggio (1571-1610), was a unique case in the Italian Painting during the 17th century, when Italy was the origin of culture, religious and scientific awareness in Europe. The influence of Caravaggio style spread across generations of painters who interpreted his character and style as a norm that expressed the Italian identity or even the European identity during the modern times. His works even became an inspiration for contemporary murals in streets and squares. This study focuses on discussing this contemporary perception of the heritage of the 17th century through the national identity restoration program of the Dutch city of “Utrecht”, represented in a number of murals that reproduce the works of “Caravaggio”, and his students. Accordingly, we could reconfigure the artistic vision in the Egyptian art heritage, in a similar way, and present it to the society in a way that preserves its identity and increases its awareness of its heritage and culture.